Did humans and natural forests coexist in close proximity? A case study of the Lateglacial and Holocene Mollusca in the Moravian Karst, Czech Republic - Juřičková, Lucie; Horáčková, Jitka; Jansová, Anna; Škodová, Jana; Kosová, Tereza; Ložek, Vojen (Boreas, 2019)
Prehistoric settlements are usually perceived as being in opposition to the natural development of the landscape. Indeed, for woodland snail assemblages in anthropogenic landscapes in central Europe, considerable impoverishment is typical. However, it remains unclear whether this has been caused by humans only or also by climate effects. From an archaeological point of view, the Moravian Karst is one of the classic prehistorical locations in central Europe, but with a more humid climate than the previously studied anthropogenic areas. To learn more about coexistence of humans and natural forests during the Lateglacial and Holocene, we analysed 11 mollusc successions covering this entire area, a unique data set for such a relatively small area. These mollusc successions show several specific features compared to the standard development known from other mid‐European areas. One is that although the Moravian Karst is not far from the Western Carpathians, Carpathian species appeared relatively late, only during the second half of the Holocene climatic optimum. Similarly, some western European and Alpine elements appeared later than expected. In contrast to this, however, a number of forest species with central European range appeared relatively early during the Lateglacial or Early Holocene. Two even survived the Last Glacial Maximum in the Moravian Karst. This would suggest an early occurrence of forest patches in a mosaic landscape. Humans have apparently inhabited this area since the Lateglacial amongst islands of forests, which later changed during the Boreal and then the climatic optimum into humid canopy forests. Thus, a mosaic of anthropogenic and natural habitats persisting in close vicinity was possible in rugged and humid landscapes practically until the Industrial Revolution.